Avaliação terapêutica com mulheres que vivenciaram violência por parceiros íntimos: verificando a autoestima - Ribeiro, Liliane Cardoso (2021)
Therapeutic Assessment (TA) is an interventional and collaborative psychological assessment process that presents direct and positive therapeutic benefits for the client, such as reducing symptoms and improving self-esteem, in addition to providing maturity to the client. Selfesteem is a personality factor related to the value a person attaches to himself and, in contexts of trauma and violence, it is usually quite fragile. Therefore, it is one of the main focuses of psychologists who work in the context of Intimate Partner Violence (IPV), which is characterized by violent attitudes taken by people in affective-sexual relationships. This violence is often suffered by heterossexual women and causes damage to physical and psychological health. Considering, then, the therapeutic benefits of TA, this research aims to verify how TA can influence the self-esteem of women who have experienced IPV. The TA process was carried out with three divorced heterossexual adult women. The three TA processes followed a semi-structure of six stages, with an average of nine to ten face-to-face sessions, which had an average duration of 90 to 120 minutes. All biosafety protocols due to the Covid19 pandemic were followed during visits that occurred during the pandemic period. The research was mixed in nature to a multiple case study, using content analysis and pre- and postintervention investigation, which served to understand the process of self-esteem change during and after TA. The instruments used in the pre- and post-intervention were the Rosenberg SelfEsteem Scale, the Jenis and Field Self-Concept Scale, the Self-Image Scale, the Self-Report Questionnaire, the Magic Ideation Scale, the Experiences in Close Relationship Scale, Inventory of Post-Traumatic Cognitions and Beck Anxiety, Depression, Hopelessness and Suicide Scales. The results showed a reduction in symptoms related to psychological distress and trauma. In addition, there was a reduction in the content related to risk and emotional factors of IPV and low self-esteem, two participants showed reliable changes in self-esteem, and one didn’t. As for the change process, the TA was able to stimulate change factors such as active participation, reflection and confrontation, presenting points of change in all its stages. Participants considered the TA process an important tool to support the fight against violence. It was then suggested that, through these factors, TA provided therapeutic benefits and positively influenced self-esteem, serving as a coping strategy in the context of IPV. Thus, this study analyzed the TA process, showing that TA can influence the self-esteem of women who have experienced IPV and trauma situations, in addition to providing data that contribute to the knowledge of how TA stimulates the process of change in the client and in the self-esteem during the assessment process.